Bromação e esterificação de fenóis de origem natural e avaliação do seu potencial fungicida frente ao fungo Colletotrichum musae - Costa, Kamille Azevedo (2024)
Brazil is one of the largest agricultural producers in the world, however, it faces major challenges in agriculture due to the incidence of diseases in plantations, mainly fungal. Chemical control is the most used in crops, however, the disordered use of agrochemicals has caused great resistance of pathogens to synthetic fungicides currently sold. In view of this, looking for new molecules that generate less environmental impact and that are more selective for a given disease is very important. Through catalytic processes, it is possible to facilitate the synthesis of new molecules, enabling the obtaining of substances with potential fungicidal activity. In this context, the present study aims to brominate and esterify phenols of natural origin, via one pot/tandem catalytic synthesis, using CuCl2 as a catalyst and acetic anhydride as an acetylating agent, and to evaluate the antifungal effect under in vitro conditions against fungus Colletotrichum musae. The catalytic process developed, depending on the substrate, can achieve conversion and selectivity of 100%, the reactions were monitored by Gas Chromatography coupled to DIC, and the synthesized products were identified by Gas Chromatography coupled to Mass Spectrometry (GC/MS) and 1H and 13C Nuclear Magnetic Resonance e. In this system, it was possible to confirm that the catalyst promotes the reaction in the first stage, and accelerates the second stage, showing that this reaction is of the tandem type. The antifungal tests with the fungus C. musae were carried out with the synthesized products derived from eugenol and showed excellent inhibitory potential, however, the synthesis product from the first stage (IC50= 94 mg/L; IC90=474 mg/L) has better antifungal action than the product from the second stage (IC50= 314 mg/L; IC90=3100 mg/L), as it completely inhibits the fungus in lower concentrations. This research demonstrated promising results, as it was possible to develop and apply an efficient and low-cost one-pot/tandem catalytic system, and with low concentrations of the synthetic product it was possible to inhibit the mycelial development of the fungus C. musae